KOMUNIKASI POLITIK DALAM PEMILIHAN GUBERNUR JAWA TIMUR (Fungsi Media Massa Sebagai Sarana Pemenangan Kandidat) - Priyowidodo, Gatut (Scriptura, 2007)
Governor election as an implementation of Act No. 32 Year 2004 as a matter of fact is a reformation mandate. Governor as the Head of a Province is not elected by Provincial People Representative Assembly (DPRD), yet it is thoroughly left to people to elect one. They decide who is the most proper to be their leader. Even at the latest development, governor candidates are not only carried on via political parties, yet based on results of Judgment of Judicial Review by Constitution Court of Law, governor candidates can be nominated through individual candidates. Therefore, it is very important take into account that every candidate must at least meet three main requirements namely principle of acceptability, principle of capability and principle of professionalism. And the last but the not the least is principle of candidate popularity. So, there is no other way to boost image and prestige of a candidate in short period of time except by considerably carrying out activities that can be covered by media. So far mass media have remained being the most effective means to improve reputation as well as able to destroy reputation by bad news reports. The article, at least argue that mass media make significant contribution to success or failure of governor candidates to occupy chair of Province 1 (one).